Prevalence and correlates of sleep disorder symptoms in psychiatric disorders - Hombali, Aditi; Seow, Esmond; Yuan, Qi; Chang, Shi Hui Sherilyn; Satghare, Pratika; Kumar, Sunita; Verma, Swapna Kamal; Mok, Yee Ming; Chong, Siow Ann; Subramaniam, Mythily (Psychiatry research, 2019)
•Symptoms of various sleep disorders are not uncommon among psychiatric patients.•Individuals with anxiety disorder were at a higher risk of having symptoms of sleep disorder.•Identifying and addressing the sleep disorders at early stages may have a positive impact on the prognosis and quality of life. Difficulty falling asleep or maintaining sleep, poor sleep quality, nightmares, and excessive daytime sleepiness are some of the key clinical symptoms of sleep disturbances observed among individuals with psychiatric illnesses. This study aimed to determine the prevalence of symptoms of sleep disorders including parasomnia, narcolepsy, obstructive sleep apnea, circadian rhythm disorder and restless leg syndrome/periodic limb movement (RLS/PLMS) and its correlates in patients with psychiatric diagnoses. Patients aged 21–65 years (n = 400) attending the outpatient clinics with a primary diagnosis of either schizophrenia, mood or anxiety disorder based on ICD-9 criteria were included in this cross-sectional study. Sociodemographic information was collected and screening questions pertaining to specific symptoms of sleep disorders were administered by a study team member. The overall prevalence of symptoms of sleep disorders in the psychiatric outpatient sample was 40.75% (163/400). The prevalence for symptoms of narcolepsy, sleep breathing disorder, PLMS/RLS, circadian rhythm disorder and parasomnia were 12.5%, 14.5%, 14.8%, 4.5%, and 13.8% respectively. These symptoms were associated with age, low physical activity, and anxiety disorder. Results highlight the high prevalence of symptoms of sleep disorders in psychiatric patients. Present study findings should be confirmed using diagnostic interviews and objective measures.